When Organic Urban Forms and Grid Systems Collide:Application of Space Syntax for Analyzing the Spatial Configuration of Barcelona, Spain. Issue 3 (1st September 2017) - Yoo, Chisun; Lee, Sugie
Abstract : Many cities around the world have experienced fast urbanization with suburban development. The organic urban forms of old towns or existing city centers have been extended with modern grid systems. However, little research has been conducted to identify the impact of modern grid forms on the organic urban structure in the city center. This study aims to examine the transformation of urban morphology using space syntax for the case study of Barcelona, Spain, which is an ideal case city because of its organic city center surrounded by an orthogonal urban system. The result showed that at the car-oriented global scale, the city center area with an organic urban form loses its importance in terms of space syntax indexes such as choice and integration values. However, the organic structure becomes more important at the pedestrian-oriented local scale. Furthermore, adding the grid structure to the original organic form increases the relative importance of the organic form in Barcelona′s city center. This finding indicates that a grid system and an organic form are not in opposition to each other, but can instead be complementary. This study implies that the integration between organic form and grid system is very important and necessary for urban regeneration in many cities.